Penggunaan Aplikasi Al Qur’an Digital Dalam Pembelajaran Pada Mata Pelajaran Qur’an Hadist : Penggunaan Aplikasi Al Qur’an Digital Dalam Pembelajaran Pada Mata Pelajaran Qur’an Hadist - Nurkholis; Asep Bambang Susanto (Program Studi Pendidikan Agama Islam, 2024)
Science develops from time to time, technology can facilitate all teaching and learning needs. However, digital technology has not been utilized optimally to study the Qur'an Hadith. This is because there are still teachers who teach monotonously using the lecture method while delivering material in class without media. This research method uses library research. Information is obtained from several sources such as magazines and books. Descriptive analysis is used to analyze the data. The research results show that learning Al-Quran Hadith through digital Al-Quran application technology is beneficial for teachers and students. The advantage of the application for teachers and students is that it provides easy access to the features of the digital Al-Quran application so that learning becomes more interactive, students can also carry out learning activities, repeat Qur'an Hadith lessons at school, at home, anytime and anywhere, such as memorizing verses and its meaning, the law of reading verse by verse.